Multiple extensive Madurella mycetomatis eumycetoma lesions: a case report and review of the literature. (6th January 2021) - Zaid, Dania M; Bakheet, Osama E; Ahmed, Eiman Siddig; Abdalati, Fatima; Mhmoud, Najwa A; Mohamed, El Samani Wadaa; Bakhiet, Sahar Mubarak; Siddig, Emmanuel Edwar; Fahal, Ahmed Hassan
Abstract: In this communication, we report on the first-ever patient presenting with 17 lesions of Madurella mycetomatis eumycetoma in different parts of the body. The reported patient is a 15-y-old female who presented to the Mycetoma Research Centre, University of Khartoum, Khartoum, Sudan, in 2017 with recurrent back and anterior abdominal wall eumycetoma lesions. They were surgically excised, and during the course of follow-up, she developed 15 other eumycetoma lesions, scattered mostly on her upper and lower limbs and gluteal region. The diagnosis of Madurella mycetomatis was confirmed by molecular identification of grains and culture, histopathological examination and ultrasound examination. The cause and the explanation of such a presentation in puzzling; it is not due to multiple subcutaneous implantations because of the lack of history of relevant local trauma. Lymphatic spread is unlikely as the distribution of the lesions is not in line with this. Haematogenous spread is a possible explanation. This rare presentation of eumycetoma poses a great challenge for diagnosis and management.